Increased Metabolic Activity on 18F-Fluorodeoxyglucose Positron Emission Tomography–Computed Tomography in Human Immunodeficiency Virus–Associated Immune Reconstitution Inflammatory Syndrome. (11th September 2018) - Hammoud, Dima A; Boulougoura, Afroditi; Papadakis, Georgios Z; Wang, Jing; Dodd, Lori E; Rupert, Adam; Higgins, Jeanette; Roby, Gregg; Metzger, Dorinda; Laidlaw, Elizabeth; Mican, JoAnn M; Pau, Alice; et al.
Abstract : High glycolytic activity and opportunistic infection load measured by 18 F-fluorodeoxyglucose positron emission tomography imaging before antiretroviral therapy initiation are associated with immune reconstitution inflammatory syndrome development in HIV+ patients, highlighting the intersect of metabolism and inflammation in HIV infection. Abstract: Background: Immune reconstitution inflammatory syndrome (IRIS) represents an unexpected inflammatory response shortly after initiation of antiretroviral therapy (ART) in some human immunodeficiency virus (HIV)–infected patients with underlying neoplasia or opportunistic infections, including tuberculosis. We hypothesized that IRIS is associated with increased glycolysis and that 18 F-fluorodeoxyglucose (FDG) positron emission tomography–computed tomography (PET/CT) could help identify high-risk subjects. Methods: In this prospective cohort study, 30 HIV-infected patients (CD4 + count <100 cells/µL) underwent FDG-PET/CT scans at baseline and 4–8 weeks after ART initiation. Ten patients developed IRIS (6 mycobacterial). Results: At baseline, total glycolytic activity, total lesion volume, and maximum standardized uptake values (SUVs) of pathologic FDG uptake (reflective of opportunistic disease burden) were significantly higher in IRIS vs non-IRIS ( P = .010, .017, and .029, respectively) and significantly correlated with soluble inflammatory biomarkers (interferon-γ, myeloperoxidase, tumor necrosis factor, interleukin 6, soluble CD14). Baseline bone marrow (BM) and spleen FDG uptake was higher in mycobacterial IRIS specifically. After ART initiation, BM and spleen mean SUV decreased in non-IRIS ( P = .004, .013) but not IRIS subjects. Our results were supported by significantly higher glucose transporter 1 (Glut-1) expression of CD4 + cells and monocytes after ART initiation in IRIS/mycobacterial IRIS compared with non-IRIS patients. Conclusions: We conclude that increased pathologic metabolic activity on FDG-PET/CT prior to ART initiation is associated with IRIS development and correlates with inflammatory biomarkers. Abnormally elevated BM and spleen metabolism is associated with mycobacterial IRIS, HIV viremia, and Glut-1 expression on CD4 + cells and monocytes. Clinical Trials Registration: NCT02147405.